EXPLORATION OF POWER STRUGGLE IN CHATTERJEE’S PALLI SAMAJ - Shrivastwa, Bimal Kishore (Srawung: Journal of Social Sciences and Humanities, 2022)
The article aims to explore the issues of power relations and power struggle in Sarat Chandra Chatterjee’s novel, Palli Samaj from a Marxist perspective. The characters, Rama, Ramesh depicted in the novel represent the proletariat living in the Bengal region of India. Although these characters do not mention that they are driven by cultural hegemony, it is noticed that their psychology is embedded with cultural hegemony and class superiority. They are fighting for power. The study applies qualitative approach to research. The paper takes the ideology of Karl Marx and Friedrich Engels as the research tool to analyze the power relations in the novel and thereby in the Indian society. It can be noticed that almost all the characters in the novel are fighting for power. Palli Samaj attempts to demonstrate how social power functions to create and continue social domination and how it further creates social prejudices, cultural hierarchy and hegemony. The chief finding is that Indian rural life is dominated by the cruel, corrupt upper-class Zamindari order, landlords to dominate the innocent lower- class peasants. The paper is expected to stand as a reference to all the scholars interested in researching Chatterjee further.